Price analysis between commodity groups of inflation in Banten province from 2008 to 2018 - Deswita Herlina; Amalia Romadhona (International Journal of Financial, Accounting, and Management, 2021)
Purpose: This study aimed to see how each commodity group's movement pattern that forms inflation between one commodity group and another, and to see any major linkages between groups of inflation-forming commodities in Banten Province. Research methodology: The research is undergone by using the Vector Auto Regressive (VAR) model approach through testing of Impulse Response Function (IRF) and Variance Decomposition (VD). Results: The results show that the inflation rate in the goods/services commodity groups in Banten Province have a dynamic relationship between one another. The group itself dominates inflationary movements in all commodity groups. Monthly time series data is used for 2008-2018 time spans. Limitation: The linkages presented as the results are performed in commodity groups; thus, further research would inform more about inter-linkage between commodities. Contribution: The insight of knowing the pattern is beneficial for implication policy in regional inflation targeting especially in Banten Province. Keywords: Inflation, IRF, VAR, VD